Ethnic and Racial Disparities in Self-Reported Personal Protective Equipment Shortages Among New York Healthcare Workers During the COVID-19 Pandemic - Armaan Sodhi, MPH; Stanford Chihuri, MPH; Christina W. Hoven, DrPH, MPH; Ezra S. Susser, MD, DrPH; Charles DiMaggio, PhD; David Abramson, PhD; Howard F. Andrews, PhD; Megan Ryan, MS; Guohua Li, MD, DrPH (Elsevier, 2024)
Introduction: To assess the association of race and ethnicity with self-reported personal protective equipment shortages during the COVID-19 pandemic among healthcare workers in New York. Methods: The COVID-19 Healthcare Personnel Study of New York was a prospective cohort study of HCWs with baseline data collected in April 2020 and follow-up data collected in February 2021. Multivariable logistic regression modeling was used to estimate the adjusted OR and 95% CIs of personal protective equipment shortages associated with race and ethnic minority status. Results: Healthcare workers of racial and ethnic minority status (n=361) were more likely than non-Hispanic White respondents (n=1,858) to report having experienced personal protective equipment shortages in the last week at baseline (36.0% vs 27.5%; p=0.001) and follow-up (13.6% vs 8.8%; p=0.005). With adjustment for demographic and clinical characteristics, racial and ethnic minority status was associated with 44% and 49% increased odds of experiencing PPE shortages at baseline (adjusted OR=1.44; 95% CI=1.10, 1.88) and follow up (adjusted OR=1.49; 95% CI=1.01, 2.21), respectively. Conclusions: Healthcare workers of racial and ethnic minority status in New York experienced more pervasive personal protective equipment shortages than their non-Hispanic White counterparts during the COVID-19 pandemic.